2022
DOI: 10.1021/acsomega.2c03820
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flavonoid Metabolism during the Process of Petal Discoloration in Three Malus Crabapple Cultivars

Abstract: Malus crabapple has high ornamental and ecological value. Here, the flavonoids in the petals of three pink Malus crabapple cultivars, Malus ‘Strawberry Parfait’ (GD), M. ‘Pink Spire’ (FY), and M. ‘Hongyi’ (HY), at the bud stage (flower buds are swollen, and the pistils and stamens are about to appear; L), full bloom stage (the flowers are fully open, and the stigma and anthers have recently appeared; S), and end bloom stage (the stigma and anthers are dry; M) were identified, and their abundances were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We did not identify any anthocyanins. Therefore, the color difference of “Golden Hook” beans after 12 days of storage may be caused by non‐anthocyanin flavonoid auxiliary pigments such as flavonoids, flavonols, and chalcones that affect color changes (Cui et al., 2022). Among them, 6‐ C ‐methylquercetin‐3‐ O ‐rutinoside, licoflavone C, licoflavone A, kushenol A, and uralenol were the five flavonoids with the largest difference in abundance between CK‐12d and SNP‐12d, and their content is higher in the purple red pods of the SNP‐12d group.…”
Section: Discussionmentioning
confidence: 99%
“…We did not identify any anthocyanins. Therefore, the color difference of “Golden Hook” beans after 12 days of storage may be caused by non‐anthocyanin flavonoid auxiliary pigments such as flavonoids, flavonols, and chalcones that affect color changes (Cui et al., 2022). Among them, 6‐ C ‐methylquercetin‐3‐ O ‐rutinoside, licoflavone C, licoflavone A, kushenol A, and uralenol were the five flavonoids with the largest difference in abundance between CK‐12d and SNP‐12d, and their content is higher in the purple red pods of the SNP‐12d group.…”
Section: Discussionmentioning
confidence: 99%
“…The layering of pigments in different solvents confirmed that both groups of pigments played a role in the petal coloration. The petal fading phenotype is observed in many other ornamental plants, such as Chrysanthemum, Brunfelsia calycina, and ornamental crabapples [21,[43][44][45]. The main cause of petal fading in these species is a decrease in pigment accumulation, and some genes are involved in this process through expression level changes.…”
Section: Discussionmentioning
confidence: 99%